Optical adhesive sheet
By using photopolymerized polymers in optical adhesive sheets, the change in adhesive force after initial contact with water is controlled, solving the problem of premature water peeling of optical adhesive sheets during use, and achieving good adhesive reliability and water reworkability.
Patent Information
- Application Number
- CN202480039382.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-06-07
- Publication Date
- 2026-01-09
AI Technical Summary
Existing optical adhesive sheets exhibit premature water peeling during use, leading to problems such as sheet bulging and peeling, which affects adhesive reliability and water reworkability.
Using photopolymer as the base polymer, the adhesive force was controlled under different conditions through initial peel test, first water peel test, second water peel test and room temperature peel test to ensure good initial adhesive reliability and subsequent water reworkability.
It achieves good adhesive reliability during initial bonding and reduces adhesive force after water contact, ensuring that the optical adhesive sheet can be easily peeled off, thus balancing adhesive reliability and water reworkability.
Smart Images

Figure CN121311560A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to optical adhesive sheets. Background Technology
[0002] Display panels, for example, have a laminated structure that includes elements such as pixel panels, polarizing films, and cover films. During the manufacturing process of the display panel, optically transparent adhesive sheets (optical adhesive sheets) are used, for example, to bond the elements contained in the laminated structure together.
[0003] On the other hand, optical adhesive sheets with water-removable properties are known. These optical adhesive sheets are those that, after being bonded to a substrate, can reduce adhesive strength by allowing droplets of an aqueous liquid (such as water droplets) to penetrate the interface between the substrate and the adhesive sheet. Such optical adhesive sheets, after being bonded to a substrate, can be easily peeled off from the substrate using water as needed. For example, in the manufacturing process of a display panel, if the adhesion of the optical adhesive sheet to the substrate is poor (positional misalignment, etc.), water can be used to peel the adhesive sheet off the substrate, and a replacement optical adhesive sheet can be used to perform the bonding work (water rework capability). Such optical adhesive sheets for display panel applications are described, for example, in Patent Document 1 below.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-23679 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] Patent Document 1 describes an optical adhesive sheet containing an acrylic-based polymer and a surfactant. The surfactant is dispersed in a free state within the adhesive sheet. In this adhesive sheet, the surfactant is present on the adhesive surface, thereby exhibiting water-repellent properties. However, in the optical adhesive sheet of Patent Document 1, due to the relatively large amount of surfactant present, water-repellent properties are exhibited immediately after the optical adhesive sheet is applied to the substrate. Such an optical adhesive sheet has the following drawback: during processing using the adhesive sheet, or during subsequent storage or transport, if water inadvertently adheres to the optical adhesive sheet on the substrate, the adhesive sheet may bulge and peel off. From the viewpoint of avoiding such drawbacks, it is sometimes desirable for the optical adhesive sheet to exhibit water-repellent properties afterward.
[0009] The present invention provides an optical adhesive sheet that can balance good adhesive reliability to the adhered objects and good water rework performance.
[0010] means for solving problems
[0011] The present invention [1] includes an optical adhesive sheet containing a photopolymer as a base polymer, wherein the adhesive force Fn1 of the optical adhesive sheet in the initial peel test described below is 1.4 N / 10 mm or more, the adhesive force Fw1 in the first water peel test described below is greater than 1.2 N / 10 mm, and the adhesive force Fw2 in the second water peel test described below is 1.2 N / 10 mm or less.
[0012] Initial peel test:
[0013] First, a small piece of the optical adhesive sheet, 10mm wide and 100mm long, is attached to an alkali glass plate made by the float glass process to obtain a laminate (preparation step).
[0014] Next, the laminate was subjected to a heat-pressurization treatment at 50°C, 0.5 MPa and for 15 minutes (heat-pressurization step).
[0015] Next, the laminate is left to stand at room temperature for 30 minutes (standing step).
[0016] Next, under the conditions of 25°C, 50% relative humidity, 180° peel angle and 300 mm / min, the adhesive sheet is pulled along one end of its length direction, thereby peeling the adhesive sheet from the alkaline glass plate and measuring the adhesive force (measurement step).
[0017] First water stripping test:
[0018] Except for the water supply step performed after the settling step and before the measurement step, the process is the same as the initial peel test. In the water supply step, 20 μL of distilled water is supplied to the alkali glass plate of the laminate in such a way that the distilled water contacts one end of the adhesive sheet at the interface between the alkali glass plate and the adhesive sheet in the longitudinal direction.
[0019] Second water stripping test:
[0020] Except for the settling step, in which the laminate is settling at room temperature for 72 hours, the process is the same as the first water stripping test.
[0021] The present invention [2] includes the optical adhesive sheet described in [1] above, wherein the optical adhesive sheet has an adhesive force Fn2 in the following room temperature peel test, and the ratio of the adhesive force Fw2 to the adhesive force Fn2 is 0.4 or less.
[0022] Room temperature peel test:
[0023] Except for the initial peel test, in which the laminate is left to stand at room temperature for 72 hours during the settling step, the process is the same.
[0024] The present invention [3] includes the optical adhesive sheet described in [1] or [2] above, wherein the adhesive force Fn2 of the optical adhesive sheet in the following room temperature peel test is 3.0 N / 10 mm or more.
[0025] Room temperature peel test:
[0026] Except for the initial peel test, in which the laminate is left to stand at room temperature for 72 hours during the settling step, the process is the same.
[0027] The present invention [4] includes an optical adhesive sheet as described in any one of [1] to [3] above, wherein the optical adhesive sheet has an adhesive force Fw3 in the third water peel test described below, the adhesive force Fw3 having a variation rate of less than 30% relative to the adhesive force Fw2.
[0028] Third water stripping test:
[0029] Except for the settling step, in which the laminate is settling at room temperature for 168 hours, the process is the same as the first water stripping test.
[0030] The present invention [5] includes the optical adhesive sheet described in any one of [1] to [4] above, wherein the photopolymer is a polymer containing a polymerizable component of a reactive surfactant.
[0031] The present invention [6] comprises the optical adhesive sheet described in any one of [1] to [5] above, wherein the optical adhesive sheet further comprises a non-reactive surfactant.
[0032] The present invention [7] includes the optical adhesive sheet described in any one of [1] to [6] above, wherein the optical adhesive sheet further contains a hydrophilic oligomer.
[0033] Invention Effects
[0034] The optical adhesive sheet of the present invention, as described above, uses a photopolymer as its base polymer. In the initial peel test, the adhesive force Fn1 is 1.4 N / 10 mm or more; in the first water peel test, the adhesive force Fw1 is greater than 1.2 N / 10 mm; and in the second water peel test, the adhesive force Fw2 is less than 1.2 N / 10 mm. With an adhesive force Fn1 (initial adhesive force without water supply) of 1.4 N / 10 mm or more and an adhesive force Fw1 (initial adhesive force with water supply) greater than 1.2 N / 10 mm, the optical adhesive sheet is not easily peeled off even when initially applied to the substrate with water, resulting in good adhesive reliability. Furthermore, the adhesive force of the optical adhesive sheet under water supply conditions gradually decreases to less than 1.2 N / 10 mm (adhesive force Fw2), thus exhibiting good water reworkability. Therefore, the optical adhesive sheet according to the present invention can achieve both good adhesive reliability to the substrate and good water reworkability. Attached Figure Description
[0035] Figure 1 This is a schematic cross-sectional view of an optical adhesive sheet according to one embodiment of the present invention.
[0036] Figure 2 The water stripping test is illustrated schematically.
[0037] Figure 3 shows Figure 1 An example of how to use the optical adhesive sheet is shown. Figure 3A This indicates the process of attaching an optical adhesive sheet to a first substrate. Figure 3B This indicates the process of joining a first substrate to a second substrate using an optical adhesive sheet. Figure 3C This indicates the ripening process. Detailed Implementation
[0038] like Figure 1 As shown, the adhesive sheet 10, as one embodiment of the optical adhesive sheet of the present invention, has a sheet shape with a predetermined thickness and extends in a direction orthogonal to the thickness direction H (plane direction). The adhesive sheet 10 has an adhesive surface 11 and an adhesive surface 12 opposite to the adhesive surface 11. Figure 1 This illustration exemplifies the state in which release liner L1 and release liner L2 are attached to the adhesive surfaces 11 and 12 of the adhesive sheet 10. Release liner L1 is disposed on the adhesive surface 11. Release liner L2 is disposed on the adhesive surface 12.
[0039] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 is a water-removable optical adhesive sheet. That is, the adhesive sheet 10 is an optical adhesive sheet that, after being bonded to an object, can reduce the adhesive force by allowing droplets of an aqueous liquid (such as water droplets) to penetrate into the interface between the object and the adhesive sheet 10. Furthermore, the adhesive sheet 10 is, for example, an optical adhesive sheet to be disposed in a light-transmitting portion of a display panel. Examples of display panels include, for example, liquid crystal panels and organic EL panels. The display panel, for example, has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. The adhesive sheet 10 is used, for example, during the manufacturing process of the display panel for bonding the elements included in the laminated structure to each other.
[0040] The adhesive sheet 10 is a sheet-like pressure-sensitive adhesive. The adhesive sheet 10 contains a photopolymer (photopolymerizable polymer) as its base polymer. Specifically, the base polymer is a polymer obtained by photopolymerization of polymerizable components such as monomers. Photopolymerization refers to a polymerization method in which polymerizable components undergo a polymerization reaction caused by irradiation with active energy rays such as ultraviolet light. Furthermore, the adhesive sheet 10 exhibits an adhesive strength Fn1 of 1.4 N / 10 mm or more in the initial peel test described below, an adhesive strength Fw1 greater than 1.2 N / 10 mm in the first water peel test described below, and an adhesive strength Fw2 of 1.2 N / 10 mm or less in the second water peel test described below.
[0041] Initial peel test:
[0042] First, a small adhesive sheet 10, 10 mm wide and 100 mm long, is attached to an alkali glass plate made using the float glass process to obtain a laminate (preparation step). In this step, the adhesive sheet is adhered to the tin side of the alkali glass plate (the same applies to other peel tests described later). Next, the laminate is subjected to heat and pressure treatment at 50°C, 0.5 MPa, and 15 minutes (heat and pressure treatment step). Next, the laminate is allowed to stand at room temperature for 30 minutes (standing step). Next, the adhesive sheet is pulled along one end along its length at 25°C, 50% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min, thereby peeling the adhesive sheet from the alkali glass plate and measuring the adhesive strength (testing step). The method for the initial peel test is more specifically described in the examples described later.
[0043] First water stripping test:
[0044] Except for the water supply step performed after the settling step and before the measurement step, the process is the same as the initial peel test. In the water supply step, 20 μL of distilled water is supplied to the alkali glass plate of the laminate in such a way that the distilled water contacts one end of the adhesive sheet at the interface between the alkali glass plate and the adhesive sheet along its length. Specifically, as... Figure 2As shown, 20 μL of distilled water 22 is supplied to the alkali glass plate 21 of the laminate W in such a way that the distilled water 22 contacts one end 10a of the adhesive piece 10A in the longitudinal direction D at the interface B between the alkali glass plate 21 and the adhesive piece 10A. The method for the first water peel test is more specifically described in the embodiments described later.
[0045] Second water stripping test:
[0046] Except for the settling step, in which the laminate is set at room temperature for 72 hours, the process is the same as the first water stripping test.
[0047] As described above, the adhesive sheet 10 uses a photopolymer as its base polymer. In the initial peel test, the adhesive force Fn1 is 1.4 N / 10 mm or more; in the first water peel test, the adhesive force Fw1 is greater than 1.2 N / 10 mm; and in the second water peel test, the adhesive force Fw2 is less than 1.2 N / 10 mm. With an adhesive force Fn1 (initial adhesive force without water supply) of 1.4 N / 10 mm or more and an adhesive force Fw1 (initial adhesive force with water supply) greater than 1.2 N / 10 mm, the adhesive sheet 10 is not easily peeled off even when initially applied to the substrate with water, resulting in good adhesive reliability. Furthermore, the adhesive force in the water peel test of the adhesive sheet 10 gradually decreases to less than 1.2 N / 10 mm (adhesive force Fw2), thus exhibiting good water reworkability. Therefore, the adhesive sheet 10 achieves both good adhesive reliability to the substrate and good water reworkability.
[0048] The adhesive strength Fn1 is preferably 3.0 N / 10 mm or more, more preferably 4.0 N / 10 mm or more, even more preferably 5.0 N / 10 mm or more, and preferably 10.0 N / 10 mm or less, more preferably 8.0 N / 10 mm or less, and even more preferably 7.2 N / 10 mm or less. When the adhesive strength Fn1 is at or above the above-mentioned lower limit value, good adhesive reliability of the adhesive sheet 10 to the adhered object can be obtained. As a method for adjusting the adhesive strength Fn1, examples include the selection of the type of base polymer in the adhesive sheet 10, the adjustment of the molecular weight, the adjustment of the degree of crosslinking, and the adjustment of the amount of compounding. As a method for adjusting these, examples include the selection of the type and adjustment of the amount of reactive surfactant, multifunctional polymerizable compound (crosslinking agent), and polymerization initiator used in the formation of the base polymer. As a method for adjusting the adhesive strength Fn1, examples include the selection of the type of component other than the base polymer in the adhesive sheet 10 and the adjustment of the amount of that component. Examples of such components include oligomers (hydrophilic oligomers, hydrophobic oligomers), non-reactive surfactants, and silane coupling agents. These modifiers also apply to the adhesive forces Fw1, Fw2, Fw3, Fn2, and Fz, which will be discussed later.
[0049] From the viewpoint of achieving good adhesive reliability of the adhesive sheet 10, the adhesive force Fw1 is preferably 1.3 N / 10 mm or more, more preferably 1.4 N / 10 mm or more, and even more preferably 1.5 N / 10 mm or more. From the viewpoint of facilitating the design that ensures the long-term stability of the adhesive sheet 10, the adhesive force Fw1 is preferably 2.5 N / 10 mm or less, more preferably 2.2 N / 10 mm or less, and even more preferably 2.0 N / 10 mm or less.
[0050] The ratio of adhesive force Fw1 to adhesive force Fn1 (Fw1 / Fn1) is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.25 or more, and preferably 0.5 or less, more preferably 0.45 or less, even more preferably 0.4 or less. When the ratio (Fw1 / Fn1) is at or above the lower limit mentioned above, good adhesive reliability can be obtained in the adhesive sheet 10. When the ratio (Fw1 / Fn1) is at or below the upper limit mentioned above, the adhesive force Fw2 and the adhesive force Fw3 (described later) of the adhesive sheet 10 can be sufficiently reduced.
[0051] The adhesive force Fw2 is preferably 1.0 N / 10 mm or less, more preferably 0.7 N / 10 mm or less, even more preferably 0.4 N / 10 mm or less, and still more preferably 0.2 N / 10 mm or less. It is also preferably 0.04 N / 10 mm or more, more preferably 0.1 N / 10 mm or more, and even more preferably 0.15 N / 10 mm or more. When the adhesive force Fw2 is below the above-mentioned upper limit, good water-repellent and water-reworkable properties can be ensured in the adhesive sheet 10. When the adhesive force Fw2 is above the above-mentioned lower limit, the lifting and peeling of the adhesive sheet 10 when water accidentally adheres to the adhered object can be suppressed.
[0052] The first rate of change of adhesive force Fw2 relative to adhesive force Fw1, expressed by the following formula, is preferably -10% or less, more preferably -20% or less, even more preferably -25% or less, and preferably -200% or more, more preferably -150% or more, and even more preferably -100% or more. A negative first rate of change means that adhesive force Fw2 is lower than adhesive force Fw1. When the first rate of change is below the above-mentioned upper limit, the adhesive sheet 10 can exhibit good water reworkability afterward. When the first rate of change is above the above-mentioned lower limit, the lifting and peeling of the adhesive sheet 10 can be suppressed in the event that water accidentally adheres to the adhesive sheet 10 to the adhered object after a certain period of time.
[0053] First rate of change (%) = [(Fw2-Fw1) / Fw1] × 100
[0054] In the first room temperature peel test described below, the adhesive sheet 10 has an adhesive force Fn2. The ratio of the adhesive force Fw2 to the adhesive force Fn2 (Fw2 / Fn2) is preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and preferably 0.004 or more, more preferably 0.01 or more. When the ratio (Fw2 / Fn2) is below the above-mentioned upper limit, the adhesive sheet 10 exhibits good water reworkability due to improved water peelability. When the ratio (Fw2 / Fn2) is above the above-mentioned lower limit, the lifting and peeling of the adhesive sheet 10 can be suppressed when water accidentally adheres to the adhesive sheet 10 on the adhered object.
[0055] First room temperature peel test:
[0056] Except for setting the settling time in the settling step to 72 hours instead of 30 minutes, it is the same as the initial peeling test.
[0057] The adhesive force Fn2 is preferably 3.0 N / 10 mm or more, more preferably 4.0 N / 10 mm or more, even more preferably 5.0 N / 10 mm or more, and preferably 10.0 N / 10 mm or less, more preferably 8.0 N / 10 mm or less, and even more preferably 7.2 N / 10 mm or less. When the adhesive force Fn2 is at or above the above-mentioned lower limit value, the adhesive reliability of the adhesive sheet 10 to the adhered object can be ensured. When the adhesive force Fn2 is at or below the above-mentioned upper limit value, the aforementioned low adhesive force Fw2 can be ensured.
[0058] In the third water peel test described below, the adhesive force Fw3 of the adhesive sheet 10 is preferably 1.0 N / 10 mm or less, more preferably 0.7 N / 10 mm or less, even more preferably 0.4 N / 10 mm or less, and still more preferably 0.2 N / 10 mm or less. It is also preferably 0.04 N / 10 mm or more, more preferably 0.1 N / 10 mm or more, and even more preferably 0.15 N / 10 mm or more. When the adhesive force Fw3 is below the aforementioned upper limit, good water peelability and water reworkability can be ensured in the adhesive sheet 10. When the adhesive force Fw3 is above the aforementioned lower limit, the lifting and peeling of the adhesive sheet 10 can be suppressed when water inadvertently adheres to the adhered object.
[0059] Third water stripping test:
[0060] Except for the settling step, in which the laminate is set at room temperature for 168 hours, the process is the same as the first water stripping test.
[0061] The second variation rate of the adhesive force Fw3 relative to the adhesive force Fw2, expressed by the following formula, is preferably 30% or less, more preferably 10% or less, even more preferably 0% or less, and preferably -200% or more, more preferably -100% or more, even more preferably -50% or more (a negative second variation rate means that the adhesive force Fw3 is lower than the adhesive force Fw2). This configuration is suitable for achieving stable water reworkability in the adhesive sheet 10.
[0062] Second rate of change (%) = [(Fw3-Fw2) / Fw2] × 100
[0063] In the second room temperature peel test described below, the adhesive sheet 10 has an adhesive force Fn3. The ratio of the adhesive force Fw3 to the adhesive force Fn3 (Fw3 / Fn3) is preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and preferably 0.004 or more, more preferably 0.01 or more. When the ratio (Fw3 / Fn3) is below the above-mentioned upper limit, the adhesive sheet 10 exhibits good water reworkability due to improved water peelability. When the ratio (Fw3 / Fn3) is above the above-mentioned lower limit, the lifting and peeling of the adhesive sheet 10 can be suppressed when water accidentally adheres to the adhesive sheet 10 on the adhered object.
[0064] Second room temperature peel test:
[0065] Except for setting the settling time in the settling step to 168 hours instead of 30 minutes, it is the same as the initial peeling test.
[0066] The adhesive force Fn3 is preferably 3.0 N / 10 mm or more, more preferably 4.0 N / 10 mm or more, even more preferably 5.0 N / 10 mm or more, and preferably 10.0 N / 10 mm or less, more preferably 8.0 N / 10 mm or less, and even more preferably 7.2 N / 10 mm or less. When the adhesive force Fn3 is at or above the lower limit value mentioned above, the adhesion reliability between the adhesive sheet 10 and the adhered object can be ensured. When the adhesive force Fn3 is at or below the upper limit value mentioned above, the aforementioned low adhesive force Fw3 can be ensured.
[0067] From the viewpoint of achieving good adhesive reliability of the adhesive sheet 10 under high temperature and high humidity, the adhesive force Fz of the adhesive sheet 10 in the following high temperature and high humidity peel test is preferably 1.1 N / 10 mm or more, and more preferably 1.2 N / 10 mm or more.
[0068] High temperature and high humidity peel test:
[0069] Except for the following, the procedure is the same as the initial peel test. A high-temperature and high-humidity treatment step is performed after the settling step and before the measurement step. In this step, the laminate after the settling step is subjected to high-temperature and high-humidity treatment at 60°C and 93% relative humidity for 15 minutes. In the measurement step, instead of the first condition described above, a 180° peel test is performed under the second condition (60°C, 93% relative humidity, peel angle 180°, and pulling speed 300 mm / min).
[0070] Adhesive sheet 10 is a sheet-like pressure-sensitive adhesive formed from an adhesive composition. Adhesive sheet 10 (adhesive composition) contains at least the aforementioned base polymer.
[0071] The base polymer is the adhesive component that exhibits adhesive properties in the adhesive sheet 10. Examples of base polymers include: acrylic polymers, polysiloxane polymers, polyester polymers, polyurethane polymers, polyamide polymers, polyvinyl ether polymers, vinyl acetate / vinyl chloride copolymers, modified polyolefin polymers, epoxy polymers, fluorinated polymers, and rubber polymers. From the viewpoint of ensuring good transparency and adhesion of the adhesive sheet 10, acrylic polymers are preferred as the base polymer. Acrylic polymers are copolymers containing polymerizable components of (meth)acrylate in a proportion of 50% by mass or more. "(meth)acrylate" refers to acrylic acid and / or methacrylic acid.
[0072] In this embodiment, the acrylic polymer is a polymer (photopolymer) obtained by photopolymerization of a polymerizable component comprising a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent. The polymerizable component preferably comprises a reactive surfactant. That is, the photopolymer, as the base polymer, is a polymer containing a polymerizable component comprising a reactive surfactant. Examples of acrylic polymers include: partial polymers obtained by photopolymerization of monofunctional monomers (a mixture of monofunctional monomer polymers and unreacted monofunctional monomers), and polymers obtained by photopolymerization of polyfunctional polymerizable compounds and reactive surfactants.
[0073] Such acrylic polymers include photopolymers with photocrosslinked structures (first photopolymers). A photocrosslinked structure is a structure in which linear structures composed of units derived from monofunctional monomers are crosslinked through units derived from a crosslinking agent. The base polymer may also include photopolymers without such photocrosslinked structures (second photopolymers). Second photopolymers are polymers of monofunctional monomers.
[0074] The monofunctional monomer preferably comprises a monofunctional alkyl (meth)acrylate, more preferably a alkyl (meth)acrylate comprising an alkyl group having 1 to 20 carbon atoms. The alkyl (meth)acrylate may have a straight-chain or branched alkyl group, or it may have a cyclic alkyl group (alicyclic alkyl group).
[0075] Examples of linear or branched alkyl esters of (meth)acrylate include: methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, neopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, isooctyl methacrylate, and methpropylene. Nonyl acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, undecyl acrylate, dodecyl acrylate, isotridecyl acrylate, tetradecyl acrylate, isotetradecyl acrylate, pentadecyl acrylate, hexadecyl acrylate, heptadecanyl acrylate, octadecyl acrylate, isooctadecyl acrylate, and nonadecanyl acrylate.
[0076] Examples of alkyl (meth)acrylates having an alicyclic alkyl group include: cycloalkyl (meth)acrylates, alkyl (meth)acrylates having a bicyclic aliphatic hydrocarbon ring, and alkyl (meth)acrylates having three or more aliphatic hydrocarbon rings. Examples of cycloalkyl (meth)acrylates include: cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate. Examples of alkyl (meth)acrylates having a bicyclic aliphatic hydrocarbon ring include: isobornyl (meth)acrylate. Examples of alkyl (meth)acrylates having three or more aliphatic hydrocarbon rings include: tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0077] Monofunctional alkyl (meth)acrylates can be used alone or in combination with two or more. Preferably, the monofunctional alkyl (meth)acrylate is an alkyl acrylate having an alkyl group having 3 to 12 carbon atoms, more preferably at least one selected from the group consisting of n-butyl acrylate (BA) and n-octyl acrylate (NOAA).
[0078] From the viewpoint of appropriately exhibiting basic properties such as adhesion in the adhesive sheet 10, the proportion of monofunctional (meth)acrylate alkyl esters in the polymerizable component is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and more preferably 85% by mass or more. This proportion is, for example, 99% by mass or less.
[0079] Monofunctional monomers may include copolymerizable monomers capable of copolymerizing with monofunctional alkyl (meth)acrylates. Examples of copolymerizable monomers include those containing polar groups. Examples of monomers containing polar groups include hydroxyl-containing monomers, carboxyl-containing monomers, and monomers with nitrogen-containing rings. Monomers containing polar groups contribute to the modification of acrylic polymers, such as ensuring the cohesiveness of acrylic polymers.
[0080] Examples of hydroxyl-containing monomers include: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylaurate (meth)acrylate. The hydroxyl-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (2HEA) and 4-hydroxybutyl acrylate (4HBA).
[0081] From the viewpoint of ensuring cohesiveness in the adhesive sheet 10, the proportion of hydroxyl-containing monomers in the polymerizable component is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more. From the viewpoint of adjusting the polarity of the acrylic polymer (which relates to the compatibility of various additive components in the adhesive sheet 10 with the acrylic polymer), this proportion is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.
[0082] Examples of carboxyl-containing monomers include: acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0083] From the viewpoint of ensuring cohesion in the adhesive sheet 10 and adhesion of the adhesive sheet 10 to the adherend, the proportion of carboxyl-containing monomers in the polymerizable component is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. From the viewpoint of adjusting the glass transition temperature of the acrylic polymer and avoiding the risk of corrosion of the adherend due to acid, this proportion is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less.
[0084] Examples of monomers having a nitrogen-containing ring include: N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrrazine, N-vinylpyrrole, N-vinylimidazolium, N-vinylpyrazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-pyrazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisopyrazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen-containing ring is preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone (NVP) and acryloylmorpholine (ACMO).
[0085] From the viewpoint of ensuring cohesion in the adhesive sheet and adhesion of the adhesive sheet to the adhered object, the proportion of monomers having nitrogen-containing atomic rings in the polymerizable component is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more. From the viewpoint of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (which relates to the compatibility of various additive components in the adhesive sheet with the acrylic polymer), this proportion is preferably 10% by mass or less, more preferably 5% by mass or less.
[0086] Examples of polyfunctional polymerizable compounds include polyfunctional monomers containing two or more olefinic unsaturated double bonds in one molecule. Examples of polyfunctional monomers include polyfunctional (meth)acrylates. Examples of polyfunctional (meth)acrylates include difunctional (meth)acrylates, trifunctional (meth)acrylates, and polyfunctional (meth)acrylates with four or more functions.
[0087] Examples of bifunctional (meth)acrylates include: ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, glycerol dimethacrylate, neopentyl glycol dimethacrylate, stearic acid-modified pentaerythritol dimethacrylate, dihydrodicyclopentadienyl diacrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).
[0088] Examples of trifunctional (meth)acrylates include: trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tri(acryloyloxyethyl)isocyanurate.
[0089] Examples of polyfunctional (meth)acrylates with more than four functions include: di(trimethylolpropane)tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.
[0090] The polyfunctional polymerizable compound can be used alone or in combination of two or more. The preferred polyfunctional polymerizable compound is dipentaerythritol hexaacrylate (DPHA).
[0091] The proportion of the polyfunctional polymerizable compound in the polymerizable component is preferably 0.01% by mass or more, more preferably 0.04% by mass or more, even more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, even more preferably 0.8% by mass or more, and preferably 2% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.2% by mass or less. When the amount of the polyfunctional polymerizable compound is at or above the above-mentioned lower limit, the cohesive force in the adhesive sheet 10 is improved, and the adhesive reliability of the adhesive sheet 10 after being bonded to the adhered object is improved. When the amount of the polyfunctional polymerizable compound is below the above-mentioned upper limit, the wettability of the adhesive sheet 10 to the adhered object can be ensured, and the initial adhesive force of the adhesive sheet 10 to the adhered object can be ensured.
[0092] Examples of reactive surfactants include anionic reactive surfactants, cationic reactive surfactants, and nonionic reactive surfactants.
[0093] Anionic reactive surfactants are surfactants that become reactive by introducing free radical polymerizable functional groups into anionic nonreactive surfactants. Examples of anionic nonreactive surfactants include: higher fatty acid salts, alkyl aryl sulfonates, alkyl sulfate salts, polyethylene oxide alkyl ether sulfate salts, and polyethylene oxide alkyl aryl ether sulfate salts. Examples of higher fatty acid salts include sodium oleate. Examples of alkyl aryl sulfonates include sodium dodecylbenzene sulfonate. Examples of alkyl sulfate salts include sodium lauryl sulfate and ammonium lauryl sulfate. Examples of polyethylene oxide alkyl ether sulfate salts include sodium polyethylene oxide lauryl ether sulfate. Examples of polyethylene oxide alkyl aryl ether sulfate salts include sodium polyethylene oxide nonylphenyl ether sulfate. Free radical polymerizable functional groups include: alkenyl, acryloyl, methacryl, vinyl, vinyl ether, and allyl ether.
[0094] Cationic reactive surfactants are surfactants that become reactive by introducing free radical polymerizable functional groups into cationic non-reactive surfactants. Examples of cationic non-reactive surfactants include alkyl trimethylammonium salts, alkyl benzalkonium salts, alkyl dimethyl benzylammonium salts, and alkyl dimethyl ethylammonium ethyl sulfates.
[0095] Nonionic reactive surfactants are surfactants that become reactive by introducing free radical polymerizable functional groups into nonionic nonreactive surfactants. Examples of nonionic nonreactive surfactants include: polyethylene oxide alkyl ethers, polyethylene oxide alkylphenyl ethers, sorbitan higher fatty acid esters, polyethylene oxide sorbitan higher fatty acid esters, polyethylene oxide higher fatty acid esters, and glycerol higher fatty acid esters. Examples of polyethylene oxide alkyl ethers include: polyethylene oxide lauryl ether and polyethylene oxide stearyl ether. Examples of polyethylene oxide alkylphenyl ethers include: polyethylene oxide octylphenyl ether and polyethylene oxide nonylphenyl ether. Examples of sorbitan higher fatty acid esters include: sorbitan monolaurate, sorbitan monostearate, and sorbitan trioleate. Examples of polyethylene oxide sorbitan higher fatty acid esters include: polyethylene oxide sorbitan monolaurate. Examples of higher fatty acid esters of polyethylene oxide include polyethylene monolaurate and polyethylene monostearate. Examples of higher fatty acid esters of glycerol include glycerol monooleate and glycerol monostearate.
[0096] Reactive surfactants can be used alone or in combination with two or more. Anionic reactive surfactants are preferred. Anionic reactive surfactants and other types of reactive surfactants can also be used in combination.
[0097] Commercially available products can be used as reactive surfactants. Examples of commercially available anionic reactive surfactants include: Aqualon KH-10, KH-20, HS-05, and HS-10 manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; Adeka Reasoap SR-10N, SR-20N, SDX-222, and SDX-223 manufactured by ADEKA Co., Ltd.; and ACRIT 8WX-046-NS manufactured by Taisei Fine Chemicals Co., Ltd. Other commercially available reactive surfactants include: Amino Ion RE1000L, RE3000MA, and RE3000TG manufactured by Nippon Emulsifier Co., Ltd.; LATEMUL PD-104, PD-105, PD-420, PD-430, and PD-450 manufactured by Kao Corporation; and Antox MS-60 and MS-2N manufactured by Nippon Emulsifier Co., Ltd.
[0098] The proportion of reactive surfactant in the polymerizable component is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more. It is also preferably 0.9% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.7% by mass or less. When the proportion of reactive surfactant is at or above the aforementioned lower limit, the adhesive force Fw2 of the adhesive sheet 10 can be reduced, ensuring subsequent water reworkability. When the proportion of reactive surfactant is at or above the aforementioned lower limit, it is possible to prevent the adhesive forces Fn1 and Fn2 of the adhesive sheet 10 from becoming too low.
[0099] In this embodiment, acrylic polymers are formed by photopolymerization of a polymerizable component. The polymerizable component (containing a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent) can be polymerized in one step or in multiple steps. In the multi-step polymerization method, firstly, a prepolymer composition (prepolymerization) containing a portion of the polymer (a mixture of the polymer of the monofunctional monomer and unreacted monofunctional monomers) is prepared by polymerizing the monofunctional monomer. Next, a polyfunctional polymerizable compound as a crosslinking agent and a reactive surfactant are added to the prepolymer composition, and then a polymerization reaction (main polymerization) is carried out in a reaction system containing the portion of the polymer, the polyfunctional polymerizable compound, and the reactive surfactant. In photopolymerization, a photopolymerization initiator can be used.
[0100] Examples of photopolymerization initiators include: free radical photopolymerization initiators, cationic photopolymerization initiators, and anionic photopolymerization initiators.
[0101] Examples of free radical photopolymerization initiators include: acylphosphine oxide photopolymerization initiators, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-keto alcohol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzoyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanone photopolymerization initiators.
[0102] Examples of acylphosphine oxide photopolymerization initiators include: bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of benzoin ether photopolymerization initiators include: benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethane-1-one. Examples of acetophenone photopolymerization initiators include: 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-keto alcohol photopolymerization initiators include 2-methyl-2-hydroxyphenylacetone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime. Examples of benzoin photopolymerization initiators include benzoin. Examples of benzoyl photopolymerization initiators include benzoyl. Examples of benzophenone photopolymerization initiators include benzoyl. Examples of benzophenone photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and poly(vinylbenzophenone). Examples of ketal photopolymerization initiators include benzoyl dimethyl ketal. Examples of photopolymerization initiators for thioxanthone include: thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone. The photopolymerization initiator can be used alone or in combination of two or more. Preferably, the photopolymerization initiator is at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-1,2-diphenylethane-1-one, and 1-hydroxycyclohexylphenyl ketone.
[0103] The amount of photopolymerization initiator relative to 100 parts by mass of the polymerizable component is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.08 parts by mass or more, and preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less. When the amount of photopolymerization initiator is at or above the aforementioned lower limit, a cross-linked network with sufficient cross-linking density can be formed in the acrylic polymer, thereby ensuring the adhesive strength of the adhesive sheet 10. In addition, when the amount of photopolymerization initiator is at or above the aforementioned lower limit, the coagulation and destruction of the adhesive surface of the adhesive sheet 10 when peeling the adhesive sheet 10 from the adhered object can be suppressed. This helps to ensure, for example, water reworkability. When the amount of photopolymerization initiator is below the aforementioned upper limit, the generation of multiple polymerization initiation sites during photopolymerization can be suppressed, thereby forming a long-distance and continuous cross-linked network in the acrylic polymer. This helps to ensure, for example, initial adhesive strength. When the acrylic polymer is photopolymerized by prepolymerization and main polymerization, the photopolymerization initiator can be added after prepolymerization and during main polymerization. In this case, relative to 100 parts by mass of the monofunctional monomer, the amount of photoinitiator in the prepolymerization is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.08 parts by mass or more, and preferably 0.3 parts by mass or less, even more preferably 0.2 parts by mass or less. Relative to 100 parts by mass of the polymerizable component, the amount of photoinitiator added during the main polymerization (additional photoinitiator) is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, and preferably 0.1 parts by mass or less, even more preferably 0.07 parts by mass or less, and even more preferably 0.05 parts by mass or less.
[0104] From the viewpoint of ensuring the cohesiveness of the adhesive sheet 10, the weight-average molecular weight of the base polymer is preferably 500,000 or more, more preferably 800,000 or more, further preferably 1,000,000 or more, and even more preferably 1,500,000 or more. The weight-average molecular weight of the base polymer is determined by gel permeation chromatography (GPC) and calculated by conversion to polystyrene.
[0105] From the viewpoint of ensuring sufficient flexibility of the adhesive sheet 10, the glass transition temperature Tg1 of the base polymer is preferably below 0°C, more preferably below -20°C, further preferably below -40°C, and even more preferably below -45°C. The glass transition temperature Tg1 is, for example, above -80°C.
[0106] The glass transition temperature (Tg) of a basic polymer can be calculated using the theoretical value based on the Fox formula. The Fox formula is the relationship between the Tg of the polymer and the Tgi of the homopolymer of the monomers constituting the polymer. In the Fox formula, Tg represents the glass transition temperature (°C) of the polymer, Wi represents the weight fraction of monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of the homopolymer formed from monomer i. The glass transition temperature of the homopolymer can be obtained from literature. For example, the glass transition temperatures of various homopolymers listed in *Polymer Handbook* (4th edition, John Wiley & Sons, Inc., 1999) and "New Polymer Library 7: Introduction to Synthetic Resins for Coatings" (by Kyozo Kitaoka, Polymer Journal, 1995) can be used. Alternatively, the glass transition temperature of the homopolymer of the monomer can be calculated using the method specifically described in Japanese Patent Application Publication No. 2007-51271.
[0107] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]
[0108] The adhesive sheet 10 may contain oligomers. Examples of oligomers include hydrophilic oligomers and hydrophobic oligomers. A hydrophilic oligomer is a polymer in which the monomeric component comprises a hydrophilic monomer at a proportion of 3% by mass or more. A hydrophobic oligomer is a polymer in which the monomeric component comprises a hydrophilic monomer at a proportion of less than 3% by mass. The weight-average molecular weight of the oligomer is, for example, 1000 or more and 30000 or less. The weight-average molecular weight of the oligomer is determined by gel permeation chromatography (GPC) and calculated using polystyrene conversion.
[0109] When the base polymer is an acrylic polymer, acrylic oligomers are preferred as oligomers. That is, hydrophilic oligomers are preferably hydrophilic acrylic oligomers. Hydrophobic oligomers are preferably hydrophobic acrylic oligomers. Acrylic oligomers are oligomers that are polymers containing alkyl (meth)acrylate monomers in a proportion of 50% by mass or more.
[0110] The hydrophilic acrylic oligomer is preferably a polymer comprising a monomer component of an alkyl (meth)acrylate having a chain alkyl group ((meth)acrylate chain alkyl ester), an alkyl (meth)acrylate having an alicyclic alkyl group ((meth)acrylate alicyclic alkyl ester), and a hydrophilic monomer. Specific examples of alkyl (meth)acrylates include, for instance, the alkyl (meth)acrylates described above as monomer components of the acrylic polymer. Examples of hydrophilic monomers include, for instance, hydroxyl-containing monomers and carboxyl-containing monomers. Specific examples of hydroxyl-containing monomers and carboxyl-containing monomers include, for instance, the hydroxyl-containing monomers and carboxyl-containing monomers described above as monomer components of the acrylic polymer.
[0111] From the viewpoint of high glass transition temperature and high compatibility with the base polymer, methyl methacrylate (MMA) is preferred as a (meth)acrylate alkyl chain ester. The (meth)acrylate cycloalkyl ester is preferably at least one selected from the group consisting of tetrahydrodicyclopentadienyl acrylate (DCPA), tetrahydrodicyclopentadienyl methacrylate (DCPMA), cyclohexyl acrylate (CHA), and cyclohexyl methacrylate (CHMA). The hydrophilic monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl methacrylate (HPMA), and 4-hydroxybutyl methacrylate (HBMA). That is, the acrylic oligomer is preferably a polymer containing a monomer component comprising at least one selected from the group consisting of DCPA, DCPMA, CHA, and CHMA, at least one selected from the group consisting of HEMA, HPMA, and HBMA, and MMA.
[0112] The proportion of (meth)acrylate cyclic alkyl esters in the monomer component of the hydrophilic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and preferably 80% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less. A proportion of (meth)acrylate cyclic alkyl esters at or above the aforementioned lower limit helps ensure the adhesive strength and cohesiveness of the adhesive sheet 10. A proportion of (meth)acrylate cyclic alkyl esters at or below the aforementioned upper limit helps ensure the compatibility between the acrylic polymer and the hydrophilic oligomer in the adhesive sheet 10. The proportion of (meth)acrylate chain alkyl esters in the monomer component of the hydrophilic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and preferably 80% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less. A proportion of (meth)acrylate chain alkyl esters at or above the aforementioned lower limit helps ensure the compatibility between the acrylic polymer and the hydrophilic oligomer in the adhesive sheet 10. The proportion of (meth)acrylate alkyl esters below the aforementioned upper limit helps ensure the adhesive strength and cohesiveness of the adhesive sheet 10. The proportion of hydrophilic monomers in the monomer component of the hydrophilic acrylic oligomer is preferably 6% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 12% by mass or less. When the proportion of hydrophilic monomers is at or above the aforementioned lower limit, the adhesive strength and cohesiveness of the adhesive sheet 10 can be ensured.
[0113] When the proportion of hydrophilic monomers is below the above-mentioned upper limit, the compatibility of acrylic polymers and hydrophilic oligomers in adhesive sheet 10 can be ensured.
[0114] Hydrophilic acrylic oligomers are obtained by polymerizing the monomer components of the acrylic oligomer (the same applies to hydrophobic acrylic oligomers, which will be described later). Examples of polymerization methods include solution polymerization, active energy radiation polymerization (e.g., UV polymerization), bulk polymerization, and emulsion polymerization. In the polymerization of acrylic oligomers, polymerization initiators can be used, and chain transfer agents can be used to adjust the molecular weight.
[0115] Relative to 100 parts by weight of the base polymer, the content of hydrophilic oligomer in the adhesive sheet 10 is preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, even more preferably 0.4 parts by weight or more, and preferably 5 parts by weight or less, more preferably 4 parts by weight or less, and even more preferably 3 parts by weight or less. When the content of hydrophilic oligomer is at or above the aforementioned lower limit, the adhesive strength of the adhesive sheet 10 (especially the adhesive strength under high temperature and high humidity conditions) can be improved. When the content of hydrophilic oligomer is at or below the aforementioned upper limit, the transparency of the adhesive sheet 10 can be ensured. In the adhesive sheet 10, if there is too much oligomer, due to the decrease in the compatibility of the oligomer, there is a tendency for the haze to increase and the transparency to decrease.
[0116] The hydrophobic acrylic oligomer is preferably a polymer containing monomer components of (meth)acrylate chain alkyl esters and (meth)acrylate cycloalkyl esters. MMA is preferred as the (meth)acrylate chain alkyl ester from the perspective of high glass transition temperature and high compatibility with the base polymer. Tetrahydrodicyclopentadienyl acrylate, tetrahydrodicyclopentadienyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred as the (meth)acrylate cycloalkyl ester. That is, the acrylic oligomer is preferably a polymer containing monomer components of one or more selected from the group consisting of tetrahydrodicyclopentadienyl acrylate, tetrahydrodicyclopentadienyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and MMA.
[0117] The proportion of (meth)acrylate cyclic alkyl esters in the monomer component of the hydrophobic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and preferably 90% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less. A proportion of (meth)acrylate cyclic alkyl esters at or above the aforementioned lower limit helps ensure the adhesive strength and cohesiveness of the adhesive sheet 10. A proportion of (meth)acrylate cyclic alkyl esters at or below the aforementioned upper limit helps ensure the compatibility of the acrylic polymer in the adhesive sheet 10 with the hydrophobic oligomer. The proportion of (meth)acrylate chain alkyl esters in the monomer component of the hydrophobic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and preferably 90% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less. A proportion of (meth)acrylate chain alkyl esters at or above the aforementioned lower limit helps ensure the compatibility of the acrylic polymer in the adhesive sheet 10 with the hydrophobic oligomer. The proportion of (meth)acrylic acid chain alkyl esters below the above upper limit helps to ensure the adhesion and cohesion of adhesive sheet 10.
[0118] Relative to 100 parts by weight of the base polymer, the content of hydrophobic oligomer in the adhesive sheet 10 is preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, even more preferably 0.4 parts by weight or more, and preferably 5 parts by weight or less, more preferably 4 parts by weight or less, and even more preferably 3 parts by weight or less. When the content of hydrophobic oligomer is at or above the aforementioned lower limit, the adhesive strength of the adhesive sheet 10 can be improved. When the content of hydrophobic oligomer is at or below the aforementioned upper limit, the transparency of the adhesive sheet 10 can be ensured.
[0119] The adhesive sheet 10 preferably contains hydrophilic oligomers, more preferably it contains both hydrophilic and hydrophobic oligomers. The total content of the hydrophilic and hydrophobic oligomers in the adhesive sheet 10, relative to 100 parts by weight of the base polymer, is preferably 0.2 parts by weight or more, more preferably 0.6 parts by weight or more, even more preferably 0.8 parts by weight or more, and preferably 5 parts by weight or less, more preferably 4 parts by weight or less, even more preferably 3 parts by weight or less. When the total content of oligomers is at or above the aforementioned lower limit, the adhesive strength of the adhesive sheet 10 can be improved. When the total content of oligomers is at or below the aforementioned upper limit, the transparency of the adhesive sheet 10 can be ensured.
[0120] The adhesive sheet 10 preferably contains a non-reactive surfactant. Examples of non-reactive surfactants include the anionic and nonionic non-reactive surfactants mentioned above regarding reactive surfactants. Commercially available anionic non-reactive surfactants include, for example, Hytenol LA-10, LA-12, and LA-16 manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd. Commercially available nonionic non-reactive surfactants include, for example, RHEODOL TW-L120, L106, and TW-P120 manufactured by Kao Corporation; S-970, S-1170, and S-1570 manufactured by Mitsubishi Chemical Food Co., Ltd.; and NIKKOL TW-10, TW-20, and BWA-5 manufactured by Nikko Chemical Co., Ltd. When the reactive surfactant is anionic, the non-reactive surfactant is preferably a nonionic non-reactive surfactant.
[0121] The proportion of non-reactive surfactant in the adhesive sheet 10 is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.07% by mass or more, and preferably 0.5% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.2% by mass or less. When the proportion of non-reactive surfactant is at or above the above-mentioned lower limit, the adhesive force Fw2 of the adhesive sheet 10 can be reduced, thus ensuring subsequent water reworkability. When the proportion of reactive surfactant is at or above the above-mentioned lower limit, the reduction of the adhesive force of the adhesive sheet 10 under high temperature and high humidity environments can be suppressed.
[0122] The adhesive sheet 10 may contain other components. Examples of such other components include silane coupling agents, ultraviolet absorbers, antioxidants, and rust inhibitors.
[0123] Examples of silane coupling agents include, for example, silane coupling agents containing epoxy groups. Examples of silane coupling agents containing epoxy groups include, for example, 3-epoxypropoxydialkyldialkoxysilane and 3-epoxypropoxyalkyltrialkoxysilane. Examples of 3-epoxypropoxydialkyldialkoxysilanes include, for example, 3-epoxypropoxypropylmethyldimethoxysilane and 3-epoxypropoxypropylmethyldiethoxysilane. Examples of 3-epoxypropoxyalkyltrialkoxysilanes include, for example, 3-epoxypropoxypropyltrimethoxysilane and 3-epoxypropoxypropyltriethoxysilane. 3-epoxypropoxyalkyltrialkoxysilane is preferred as a silane coupling agent, and more preferably, 3-epoxypropoxypropyltrimethoxysilane. Silane coupling agents can be used alone or in combination of two or more. From the viewpoint of suppressing the adhesive sheet 10 and exhibiting good water-repellent properties for adhesion to glass, the proportion of silane coupling agent in the adhesive sheet 10 is preferably 3% by mass or less, more preferably 1% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0.0% by mass.
[0124] From the viewpoint of ensuring sufficient adhesion to the adhered objects, the thickness of the adhesive sheet 10 is preferably 10 μm or more, more preferably 20 μm or more. From the viewpoint of the operability and ease of cutting of the adhesive sheet 10, the thickness of the adhesive sheet 10 is preferably 500 μm or less, more preferably 400 μm or less, further preferably 300 μm or less, even more preferably 200 μm or less, and even more preferably 150 μm or less.
[0125] The total light transmittance of the adhesive sheet 10 is preferably 90% or more, more preferably 92% or more, and, for example, 100% or less. When the total light transmittance of the adhesive sheet 10 is above the aforementioned lower limit, the transparency required for an optical adhesive sheet used in a display panel can be ensured. The total light transmittance of the adhesive sheet 10 is, for example, 100% or less. The total light transmittance can be measured according to JIS K7375 (2008).
[0126] The release liner L1 is, for example, a flexible, transparent resin film. Materials for the release liner L1 include, for example, polyester resin, polyolefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, cellulose resin, and polystyrene resin. Examples of polyester resins include, for example, polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resins include polyethylene, polypropylene, and cyclic olefin polymers (COP). From the viewpoint of transparency and strength, polyester resin is preferred as the material for the release liner L1, and PET is more preferred. The surface of the adhesive sheet 10 side of the release liner L1 is preferably treated with a release agent. Examples of release treatments include, for example, silicone release treatment, long-chain alkyl acrylate release treatment, and fluorinated release treatment.
[0127] The release liner L2 is a flexible, transparent resin film. Materials used for the release liner L2 include, for example, those described above for the release liner L1. From the viewpoint of transparency and strength, polyester resin is preferred for the release liner L2, and PET is more preferred. The surface of the adhesive sheet 10 side of the release liner L2 is preferably treated with a release agent. The release treatment described above for the release liner L1 can be used as an example.
[0128] The adhesive sheet 10 can be manufactured, for example, as follows.
[0129] First, the above-described adhesive composition is prepared. Specifically, a prepolymer composition is obtained by irradiating a mixture (liquid) containing the above-described monofunctional monomer and photopolymerization initiator with ultraviolet light, thereby photopolymerizing a portion of the monofunctional monomer in the mixture. Examples of light sources for ultraviolet irradiation include ultraviolet LED lamps, high-pressure mercury lamps, black lamps, and metal halide lamps. Additionally, a wavelength cutoff filter for blocking a portion of the wavelength range of light emitted from the light source may be used during ultraviolet irradiation as needed. The illuminance during ultraviolet irradiation is, for example, 5 mW / cm². 2 ~200mW / cm 2 The cumulative irradiation intensity is, for example, 100 mJ / cm². 2 ~5000mJ / cm2 Ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 Pa·s to about 25 Pa·s. This viscosity is measured using a Type B viscometer under the conditions of rotor No. 5, rotor speed 10 rpm, and temperature 30°C. The prepolymer composition contains a photopolymer of a monofunctional monomer (the aforementioned second photopolymer) and a monofunctional monomer that has not undergone polymerization (residual monomer). Furthermore, the prepolymer composition is solvent-free. Next, a polyfunctional polymerizable compound, a reactive surfactant, and other components as needed are added to the prepolymer composition. Examples of other components include, for instance, additional photopolymerization initiators, reactive surfactants, silane coupling agents, and antioxidants. This yields an adhesive composition. The adhesive composition is solvent-free, and therefore a solvent-free adhesive composition.
[0130] Next, an adhesive composition is applied to the release liner L1 to form a coating film, and then the release liner L2 is bonded onto the coating film on the release liner L1. Examples of methods for applying the adhesive composition include: roller coating, licker coating, gravure coating, reverse coating, roller brush coating, spray coating, dip roller coating, doctor blade coating, doctor knife coating, air knife coating, curtain coating, die lip coating, and die-cutting.
[0131] Next, the coating between the release liner L1 and L2 is photocured by irradiating it with ultraviolet light to form an adhesive layer. Under ultraviolet irradiation, a polymerization reaction occurs in the coating within a reaction system containing the aforementioned residual monomers and multifunctional polymerizable compounds, thereby forming a first photopolymer with a photocrosslinking structure. The adhesive layer can then be dried by heating. The drying temperature is, for example, 80°C to 150°C. The drying time is, for example, 30 seconds to 10 minutes. This drying process allows unreacted monomers within the adhesive layer to evaporate and be removed.
[0132] Through the above operations, an adhesive sheet 10 can be manufactured, in which the adhesive surfaces 11 and 12 are covered and protected by release liner L1 and L2. The release liner L1 and L2 are peeled off from the adhesive sheet 10 as needed when using the adhesive sheet 10.
[0133] Figures 3A to 3C This is an example of how to use the adhesive sheet 10.
[0134] In this method, firstly, as Figure 3A As shown, the adhesive sheet 10 is attached to one surface of the component 31 (the first adherend) in the thickness direction H (attachment process). Examples of components 31 include pixel panels in a display panel and polarizing films. This process provides the adhesive sheet 10 for bonding with other components on the component 31.
[0135] Next, as Figure 3BAs shown, the component 31 is joined to the component 32 (the second adherend) by the adhesive tab 10 on the component 31 (joining process). For example, a cover film in a display panel can be cited as an example of component 32.
[0136] Next, as Figure 3C As shown, the adhesive sheet 10 between components 31 and 32 is cured (curing process). Through this process, the bonding force between the adhesive sheet 10 and components 31 and 32 is improved. The curing temperature is, for example, 20°C to 160°C. The curing time is, for example, 1 minute to 21 days. When the curing is performed by autoclaving (heating and pressurizing treatment), the temperature is, for example, 30°C to 80°C, the pressure is, for example, 0.1 MPa to 0.8 MPa, and the treatment time is, for example, 15 minutes or more.
[0137] According to the adhesive sheet 10, after the bonding process or the curing process, the bonding state between components 31 and 32 can be easily released with water (water rework) as needed. Specifically, as described below.
[0138] By allowing water droplets to seep into the interface between component 31 and adhesive sheet 10, the adhesive force of adhesive sheet 10 on component 31 is reduced, and then component 32 with adhesive sheet 10 can be easily separated from component 31. Afterwards, for example, alternative component 32 with adhesive sheet 10 can be joined to component 31 via its adhesive sheet 10.
[0139] Alternatively, by allowing water droplets to seep into the interface between component 32 and adhesive sheet 10, the adhesive force of adhesive sheet 10 on component 32 can be reduced, and then component 31 with adhesive sheet 10 can be easily separated from component 32. Afterwards, for example, alternative component 31 with adhesive sheet 10 can be joined to component 32 via its adhesive sheet 10.
[0140] According to the adhesive sheet 10, the adhesive force Fw2 in the second water peel test is less than 1.2 / 10mm, so water rework as described above is possible, for example.
[0141] Example
[0142] The following examples illustrate the present invention in detail. However, the present invention is not limited to these examples. Furthermore, the specific values of the amount (content), physical property values, parameters, etc., described below can be replaced with the upper limit (defined as "less than" or "less than") or lower limit (defined as "more than" or "greater than") of the corresponding amount (content), physical property values, parameters, etc., described in the above "Specific Embodiments".
[0143] <Preparation of acrylic oligomer M1>
[0144] First, in a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet, a mixture containing 60 parts by mass of tetrahydrodicyclopentadienyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution. The reaction was carried out at 70°C for 2 hours under a nitrogen atmosphere, followed by a reaction at 80°C for 2 hours (polymerization reaction). Then, the reaction solution was heated at 130°C to volatilize and remove the toluene, chain transfer agent, and unreacted monomers. This yielded a solid acrylic oligomer (oligomer M1). Oligomer M1 has a weight-average molecular weight of 5100 and a glass transition temperature of 130°C. Oligomer M1 is a hydrophobic oligomer.
[0145] <Preparation of acrylic oligomer M2>
[0146] First, in a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet, a mixture containing 45 parts by mass of DCPMA, 45 parts by mass of MMA, 10 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by mass of AIBN as a thermal polymerization initiator were added to the mixture to prepare a reaction solution, and the reaction was carried out at 70°C for 2 hours under a nitrogen atmosphere, followed by a reaction at 80°C for 2 hours (polymerization reaction). Then, the reaction solution was heated at 130°C to volatilize and remove the toluene, chain transfer agent, and unreacted monomers. This yielded a solid acrylic oligomer (oligomer M2). Oligomer M2 has a weight-average molecular weight of 5300 and a glass transition temperature of 115°C. Oligomer M2 is a hydrophilic oligomer.
[0147] <Preparation of Prepolymer Compositions>
[0148] In a flask, 20 parts by weight of n-butyl acrylate (BA), 70 parts by weight of n-octyl acrylate (NOAA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA), and 2 parts by weight of N-vinyl-2-pyrrolidone (NVP) were mixed with 0.05 parts by weight of a first photopolymerization initiator (trade name "Irgacure 819", bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by BASF Japan) and 0.05 parts by weight of a second photopolymerization initiator (trade name "Irgacure 184", 1-hydroxycyclohexylphenyl ketone, manufactured by BASF Japan). The mixture was then irradiated with ultraviolet light under a nitrogen atmosphere, thereby polymerizing a portion of the monomer components in the mixture, resulting in a prepolymer composition with a polymerization rate of approximately 10%. This prepolymer composition is a partial polymer containing a photopolymer (photopolymer P1a) and unpolymerized monomer components (residual monomers).
[0149] [Example 1]
[0150] <Preparation of Adhesive Compositions>
[0151] Next, an adhesive composition was prepared by mixing 100 parts by weight of the prepolymer composition, 0.5 parts by weight of oligomer M1, 0.5 parts by weight of oligomer M2, 0.01 parts by weight of dipentaerythritol hexaacrylate (brand name "KAYARAD DPHA", manufactured by Nippon Kayaku Co., Ltd.), which is a multifunctional polymerizable compound, 0.3 parts by weight of the first reactive surfactant (brand name "ACRIT 8WX-046-NS", manufactured by Taisei Fine Chemicals Co., Ltd.), 0.1 parts by weight of the first non-reactive surfactant (brand name "RHEODOL TW-L 120", manufactured by Kao Corporation), and 0.04 parts by weight of the additional photopolymerization initiator (brand name "Irgacure 819", manufactured by BASF Japan Co., Ltd.).
[0152] <Making Adhesive Sheets>
[0153] Next, an adhesive composition is applied to the release-treated surface of a first release liner (trade name "Diafoil MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) with a release-treated surface on one side to form a coating film. Then, the release-treated surface of a second release liner (trade name "Diafoil MRN", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) with a release-treated surface on one side is bonded to the coating film on the first release liner. Next, ultraviolet light is irradiated onto the coating film between the release liners from the second release liner side, causing the coating film to photocur and form a 50 μm thick adhesive layer (UV irradiation process). During UV irradiation, a black light lamp (manufactured by Toshiba) is used as the light source, and the illuminance is set to 5.0 mW / cm². 2The cumulative irradiation intensity was set to 1500 mJ / cm. 2 In the ultraviolet irradiation process, a photopolymerization reaction is carried out in the coating film in a reaction system containing the aforementioned residual monomer and multifunctional polymerizable compound, thereby forming a photopolymer P1b having a photocrosslinked structure. Furthermore, this photopolymerization reaction occurs around the aforementioned photopolymer P1a, thus photopolymer P1b is formed around photopolymer P1a. The adhesive layer formed in this process contains photopolymer P1a and photopolymer P1b as base polymers.
[0154] Next, the first release liner is peeled off from the adhesive layer, and then the adhesive layer on the second release liner is dried in a hot air oven at 130°C for 3 minutes. This causes unreacted monomers in the adhesive layer to evaporate and be removed. Then, it is allowed to cool naturally at room temperature, and then the release-treated side of a third release liner (trade name "Diafoil MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) with a single-sided release-treated surface is bonded onto the adhesive layer on the second release liner.
[0155] Through the above operations, the adhesive sheet with release liner of Example 1 (second release liner / adhesive sheet (thickness 50μm) / third release liner) was produced.
[0156] [Example 2]
[0157] Except for the following, the adhesive sheet with a release liner of Example 2 was produced by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, the amount of the first non-reactive surfactant (RHEODOLTW-L 120) was set to 0.05 parts by weight.
[0158] [Example 3]
[0159] Except for the following, the adhesive sheet with a release liner of Example 3 was produced by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, 0.1 parts by weight of a second non-reactive surfactant (brand name "RHEODOL TW-L 106", manufactured by Kao Corporation) was used instead of the first non-reactive surfactant.
[0160] [Example 4]
[0161] Except for the following, the adhesive sheet with a release liner of Example 4 was prepared by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, 0.05 parts by weight of a second non-reactive surfactant (RHEODOL TW-L 106) was used instead of the first non-reactive surfactant.
[0162] [Comparative Example 1]
[0163] Except for the following, an adhesive sheet with a release liner of Comparative Example 1 was prepared by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, the amount of the multifunctional polymerizable compound (DPHA) was set to 0.02 parts by mass, and 0.3 parts by mass of the second reactive surfactant (Aqualon KH-10) and 0.1 parts by mass of the third reactive surfactant (brand name "Amino Ion RE3000MA", manufactured by Nippon Emulsifier Co., Ltd.) were used instead of the first reactive surfactant.
[0164] [Comparative Example 2]
[0165] Except for the following, an adhesive sheet with a release liner for Comparative Example 2 was prepared by operating in the same manner as the adhesive sheet with a release liner for Comparative Example 1. In the preparation of the adhesive composition, the amount of the multifunctional polymerizable compound (DPHA) was set to 0.045 parts by mass.
[0166] [Comparative Example 3]
[0167] Except for the following, an adhesive sheet with a release liner of Comparative Example 3 was prepared by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, no multifunctional polymerizable compound (DPHA) was added, and 0.1 parts by weight of a third reactive surfactant (Amino Ion RE3000MA) was further added.
[0168] [Comparative Example 4]
[0169] Except for the following, an adhesive sheet with a release liner of Comparative Example 4 was prepared by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, 0.75 parts by weight of a second reactive surfactant (Aqualon KH-10) was used instead of the first reactive surfactant.
[0170] [Comparative Example 5]
[0171] Except for the following, an adhesive sheet with a release liner of Comparative Example 5 was prepared by operating in the same manner as the adhesive sheet with a release liner of Example 1. In the preparation of the adhesive composition, the amount of the multifunctional polymerizable compound (DPHA) was set to 0.045 parts by mass, and 0.5 parts by mass of the second reactive surfactant (Aqualon KH-10) was used instead of the first reactive surfactant.
[0172] <Initial peel test>
[0173] Initial peel tests were performed on the adhesive sheets of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fn1 was measured. Specifically, as described below.
[0174] Preparation steps:
[0175] First, the third release liner is peeled off from the adhesive sheet (second release liner / adhesive sheet / third release liner) with the release liner. Next, the exposed adhesive sheet is bonded to a plasma-treated polyethylene terephthalate (PET) film (trade name "Lumirror S10", 50 μm thick, manufactured by Toray Industries). This yields a laminated film. In the plasma treatment, a plasma irradiation device (trade name "AP-TO5", manufactured by Sekisui Industries) is used, with the voltage set to 160V, the frequency set to 10kHz, and the processing speed set to 5000mm / min. During bonding, the adhesive sheet is pressed onto the PET film by pressing a 2kg hand roller back and forth once at 25°C. Next, a 10mm wide × 100mm long laminated film piece is cut from the laminated film. This laminated film sequentially comprises a PET film, an adhesive sheet piece, and a second release liner in the thickness direction. Then, the second release liner is peeled off from the adhesive sheet piece on the PET film. Next, the exposed adhesive sheet (10mm wide × 100mm long) is attached to the non-tin side (air side) of an alkali glass plate made by the float glass process, thus obtaining a laminate.
[0176] Heating and pressurizing steps:
[0177] Next, the laminate was subjected to heat and pressure treatment at 50°C, 0.5 MPa, and 15 minutes. This caused the adhesive sheet pieces to be pressed onto the alkali glass plate.
[0178] Let it stand:
[0179] Next, the laminate was left to stand at room temperature for 30 minutes.
[0180] Measurement steps:
[0181] Next, a 180° peel test was performed to peel the adhesive sheet from the alkali glass plate in the laminate, and the force required for peeling (peel force) was measured. A tensile testing machine (trade name "Autograph AG-50NXplus", manufactured by Shimadzu Corporation) was used in this test. Specifically, under the conditions of 25°C, 50% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min (first condition), the adhesive sheet was peeled from the alkali glass plate by pulling one end along its length, and the adhesive force was measured. The peel length was set to 50 mm, and the average value of the measured peel forces was taken as the adhesive force. The adhesive force Fn1 (N / 10 mm) measured in the initial peel test step is shown in Table 1.
[0182] <First Water Stripping Test>
[0183] A first water peel test was performed on each adhesive sheet of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fw1 was measured. The first water peel test was the same as the initial peel test described above, except that the water supply step described below was performed after the standing step and before the measurement step. The adhesive force Fw1 (N / 10mm) measured in the measurement step of the first water peel test is shown in Table 1. The ratio of adhesive force Fw1 to adhesive force Fn1 (Fw1 / Fn1) is also shown in Table 1.
[0184] Water supply steps:
[0185] For the laminate after the settling step, 20 μL of distilled water is supplied to the alkali glass plate in such a way that the distilled water contacts one end of the adhesive sheet at the interface between the alkali glass plate and the adhesive sheet in the longitudinal direction.
[0186] <First Room Temperature Peeling Test>
[0187] A first room temperature peel test was performed on each adhesive sheet of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fn2 was measured. The first room temperature peel test was the same as the initial peel test described above, except that the laminate was left to stand at room temperature for 72 hours in the standing step. The adhesive force Fn2 (N / 10mm) measured in the first room temperature peel test is shown in Table 1.
[0188] <Second Water Stripping Test>
[0189] A second water peel test was performed on each adhesive sheet of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fw2 was measured. The second water peel test was the same as the first water peel test described above, except that the laminate was allowed to stand at room temperature for 72 hours during the standing step. The adhesive force Fw2 (N / 10mm) measured in the second water peel test is shown in Table 1. The ratio of adhesive force Fw2 to adhesive force Fn2 (Fw2 / Fn2) is also shown in Table 1. The first rate of change (%) of adhesive force Fw2 relative to adhesive force Fw1 is also shown in Table 1. This rate of change was calculated using the following formula.
[0190] First rate of change (%) = [(Fw2-Fw1) / Fw1] × 100
[0191] <Second Room Temperature Peeling Test>
[0192] A second room temperature peel test was performed on each adhesive sheet of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fn3 was measured. The second room temperature peel test was the same as the initial peel test described above, except that the laminate was left to stand at room temperature for 168 hours in the standing step. The adhesive force Fn3 (N / 10mm) measured in the second room temperature peel test is shown in Table 1.
[0193] <Third Water Stripping Test>
[0194] A third water peel test was performed on each adhesive sheet of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fw3 was measured. The third water peel test was the same as the first water peel test described above, except that the laminate was allowed to stand at room temperature for 168 hours during the settling step. The adhesive force Fw3 (N / 10mm) measured in the third water peel test is shown in Table 1. The ratio of adhesive force Fw3 to adhesive force Fn3 (Fw3 / Fn3) is also shown in Table 1. The second rate of change (%) of adhesive force Fw3 relative to adhesive force Fw2 is also shown in Table 1. This rate of change was calculated using the following formula.
[0195] Second rate of change (%) = [(Fw3-Fw2) / Fw2] × 100
[0196] <High Temperature and High Humidity Peeling Test>
[0197] High-temperature and high-humidity peel tests were conducted on the adhesive sheets of Examples 1 to 4 and Comparative Examples 1 to 5, and the adhesive force Fz was measured. The high-temperature and high-humidity peel test was the same as the initial peel test except for the following: The high-temperature and high-humidity treatment step described below was performed after the standing step and before the measurement step. In the measurement step, instead of the first condition described above, a 180° peel test was performed under the conditions of 60°C, 93% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min (second condition). The adhesive force Fz (N / 10 mm) measured in the measurement step of the high-temperature and high-humidity peel test is shown in Table 1.
[0198] High temperature and high humidity treatment steps:
[0199] The laminated body after the static step was subjected to high temperature and high humidity treatment at 60°C and 93% relative humidity for 15 minutes.
[0200]
[0201] It should be noted that the above-described invention is provided as an illustrative embodiment of the present invention, but this is merely illustrative and not intended to be limiting. All modifications of the invention that will be apparent to those skilled in the art are included within the scope of the claims.
[0202] Industrial practicality
[0203] The optical adhesive sheet of the present invention is suitable for use in display panels such as liquid crystal panels and organic EL panels. Specifically, the optical adhesive sheet of the present invention is suitable for bonding components together in a laminated structure during the manufacturing process of a display panel.
[0204] Label Explanation
[0205] 10. Adhesive sheets (optical adhesive sheets)
[0206] H-thickness direction
[0207] 10a First end
[0208] 10b Second end
[0209] 11 First page
[0210] 12 Second page
[0211] 21 Alkali Glass Plate
[0212] 22 water
[0213] L1, L2 peeling pads
Claims
1. An optical adhesive sheet, wherein the optical adhesive sheet contains a photopolymerizable polymer as a base polymer, wherein, The optical adhesive sheet exhibits an adhesive force Fn1 of 1.4 N / 10 mm or more in the initial peel test described below, an adhesive force Fw1 greater than 1.2 N / 10 mm in the first water peel test described below, and an adhesive force Fw2 of 1.2 N / 10 mm or less in the second water peel test described below. Initial peel test: First, a small piece of the optical adhesive sheet, 10mm wide and 100mm long, is attached to an alkali glass plate made by the float glass method to obtain a laminate (preparation step). Next, the laminate was subjected to heat and pressure treatment at 50°C, 0.5 MPa and for 15 minutes (heat and pressure step); Next, the laminated body is left to stand at room temperature for 30 minutes (standing step); Next, under the conditions of 25°C, 50% relative humidity, 180° peel angle and 300 mm / min, the adhesive sheet is pulled along one end of its length direction, thereby peeling the adhesive sheet from the alkaline glass plate and measuring the adhesive force (measurement step). First water stripping test: Except for the water supply step performed after the settling step and before the measurement step, the process is the same as the initial peeling test; in the water supply step, 20 μL of distilled water is supplied to the alkali glass plate of the laminate in such a way that the distilled water contacts one end of the adhesive sheet at the interface between the alkali glass plate and the adhesive sheet in the longitudinal direction. Second water stripping test: Except for the settling step, in which the laminate is settling at room temperature for 72 hours, the process is the same as the first water stripping test.
2. The optical adhesive sheet according to claim 1, wherein, The optical adhesive sheet has an adhesive force Fn2 in the following room temperature peel test, wherein the ratio of the adhesive force Fw2 to the adhesive force Fn2 is 0.4 or less; Room temperature peel test: Except for the initial peel test, in which the laminate is left to stand at room temperature for 72 hours during the settling step, the process is the same.
3. The optical adhesive sheet according to claim 1, wherein, The optical adhesive sheet exhibits an adhesive force Fn2 of 3.0 N / 10 mm or higher in the following room temperature peel test. Room temperature peel test: Except for the initial peel test, in which the laminate is left to stand at room temperature for 72 hours during the settling step, the process is the same.
4. The optical adhesive sheet according to any one of claims 1 to 3, wherein, The optical adhesive sheet exhibits an adhesive force Fw3 in the third water peel test described below, wherein the rate of change of the adhesive force Fw3 relative to the adhesive force Fw2 is less than 30%. Third water stripping test: Except for the settling step, in which the laminate is settling at room temperature for 168 hours, the process is the same as the first water stripping test.
5. The optical adhesive sheet according to any one of claims 1 to 3, wherein, The photopolymer is a polymer containing polymerizable components of reactive surfactants.
6. The optical adhesive sheet according to any one of claims 1 to 3, wherein, The optical adhesive sheet also contains a non-reactive surfactant.
7. The optical adhesive sheet according to any one of claims 1 to 3, wherein, The optical adhesive sheet also contains hydrophilic oligomers.
Citation Information
Patent Citations
Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device
JP2007051271A
Optical adhesive composition and utilization thereof
JP2020023679A
Adhesive composition, adhesive sheet, and surface protective film
CN102439107A
Removable water-dispersible acrylic-based adhesive composition and adhesive sheet
CN103930509A
Aqueous emulsion, coating film, cured object, and laminate
CN106459595A
